Anatomical variations of the external jugular veins and collaterals incidentally diagnosed with computed tomography in Shih Tzu dogs - Cho, Seoyoung; Chang, Jupill; Kim, Woosuk; Eom, Kidong; Kim, Jaehwan (Frontiers in Veterinary Science, 2024)
IntroductionThe external jugular vein (EJV) is a superficial vein of the neck in dogs; its significance is evident in veterinary clinical practice, encompassing surgeries and interventional procedures. However, there have been no reports on EJV variations in canines, despite extensive studies on variations in the jugular veins in humans. This study aimed to use CT imaging to evaluate the prevalence of anatomic vascular variations of the EJVs in Shih Tzu dogs and to describe the clinical and CT characteristics of these vascular variants.MethodsThis is a retrospective, multi-center study. The medical imaging records of Shih Tzu dogs that underwent pre- and post-contrast CT examinations of the head, neck, and thorax at the Veterinary Medical Teaching Hospital, Konkuk University, and 10 referral hospitals between 2015 and 2023 were reviewed.ResultsWe defined five types of EJV vascular variants: normal (type I), unilateral hypoplasia (type II), unilateral aplasia (type III), bilateral hypoplasia (type IV), and bilateral aplasia (type V), based on the morphological and diameter differences observed in the transverse images of Shih Tzu dogs. CT images from 547 Shih Tzu dogs revealed 119 cases (21.7%) of EJV variants. Type I was observed in 428 dogs (78.2%), type II in 46 dogs (8.4%), type III in 41 dogs (7.5%), type IV in 14 dogs (2.6%), and type V in 18 dogs (3.3%). In types II–V, compensatory drainage through the internal jugular vein (IJV) was observed, often involving the medial passage of the maxillary or linguofacial veins. A moderate negative correlation (R = −0.5) was recorded between the hypoplastic EJV and the affected-side IJV (p < 0.01). Some cases exhibited other supplementary drainage routes, such as the hyoid venous arch or median thyroid vein. Additionally, 63 persistent left cranial vena cava (PLCVC) cases (11.9%) were identified among 529 Shih Tzu dogs, showing a significant association with EJV abnormalities (p < 0.05).DiscussionOverall, this study identified anatomical variants of the EJV in Shih Tzu dogs and introduced a new classification system. These findings revealed that EJV variants and compensatory tributary enlargement were more prevalent than previously recognized, emphasizing the need to consider these nuances in veterinary procedures and imaging.